Translatability Of Arabic Fixed Expressions In Three Novels Into English Using Neural Machine Translation - Mohammad Aldelaa, Abdullah Sanad (2022)
Arabic fixed expressions (AFEs) have a symbolic figurative meaning that cannot be predicted from the individual components or the literal meanings of constituent parts. Many users nowadays rely on NMT systems to translate AFEs since these systems became an essential part of the process of translation. However, Neural Machine translation (NMT) creates a sort of difficulty and challenge to those who do not have enough experience in the translation of fixed expressions like proverbs and idioms. These translation systems might create a gap between Source Language (SL) and Target Language (TL). The study investigates the syntactic structure of the Arabic Fixed Expressions (AFEs), which allows a high level of accuracy to be achieved in its translation using selected Neural Machine Translation (NMT) systems. Also, this study seeks to identify the most efficient system to render the meaning of the (AFEs) extracted from the the three novels. Moreover,